2020
DOI: 10.1038/s41598-020-59487-1
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Lens power calculation after laser refractive surgery: A Meta-Analysis

Abstract: there are an increasing number of people who have had refractive surgery now developing cataract. To compare the accuracy of different intraocular lens (IOL) power calculation formulas after laser refractive surgery (photorefractive keratectomy or laser in situ keratomileusis), a comprehensive literature search of pubMed and eMBASe was conducted to identify comparative cohort studies and case series comparing different formulas: Haigis-L, Shammas-PL, SRK/T, Holladay 1 and Hoffer Q. Seven cohort studies and thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 29 publications
0
11
0
5
Order By: Relevance
“…Additionally, both IOL power selection targeting myopic refraction and postoperative myopic refractive outcome resulted in PE being myopic. Previous studies with earlier formulas recommended targeting myopic due to hyperopic refractive surprise when calculating IOL power in eyes with previous corneal refractive surgery [27][28][29][30][31] . Recent studies have reported that it is good to make the postoperative MR close to emmetropia in eyes having general corneal curvature, and the same results were reported for eyes which have undergone corneal refractive surgery 32,33 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, both IOL power selection targeting myopic refraction and postoperative myopic refractive outcome resulted in PE being myopic. Previous studies with earlier formulas recommended targeting myopic due to hyperopic refractive surprise when calculating IOL power in eyes with previous corneal refractive surgery [27][28][29][30][31] . Recent studies have reported that it is good to make the postoperative MR close to emmetropia in eyes having general corneal curvature, and the same results were reported for eyes which have undergone corneal refractive surgery 32,33 .…”
Section: Discussionmentioning
confidence: 99%
“…the present study, eyes with extreme biometry (mean K value of 39.13 D and mean AL of 26.59 mm) showed greater PE as calculated using Barrett True-K. IOL power calculation formulas for eyes with prior corneal refractive surgery are divided into history methods, which consider pre-refractive surgery data, and no-history methods, which are used when data from the refractive surgery are not available. Although there was no signi cant difference between the two methods4,11,25 , there has been no single formula showing high accuracy in various biometry conditions including eyes after corneal refractive surgery26,27 . Recently, Whang et al reported in a retrospective study that the predictive accuracy of no-history IOL formulas depends on AL28 .…”
mentioning
confidence: 99%
“…Com a evolução das fórmulas biométricas, atualmente na quinta geração, mais dados foram incluídos no cálculo, com o intuito de melhorar sua acurácia, como a medida de profundidade da câmara anterior, espessura do cristalino, distância branco a branco, idade, refração prévia, posição efetiva da lente, entre outros. (2) Porém, mesmo levando em consideração diversos fatores, a acurácia desse exame não é perfeita, sendo comum a ocorrência de surpresas refrativas pós-operatórias, especialmente em pacientes com assimetria corneana, por exemplo, por conta de histórico prévio de cirurgia refrativa, pós-transplante de córnea, ectasias corneanas, entre outras. (2) São três as principais causas para erros na predição do poder da LIO em pacientes com cirurgia refrativa prévia: escolha da fórmula inadequada, erro na predição do poder corneano e erro do aparelho.…”
Section: Introductionunclassified
“…(2) Porém, mesmo levando em consideração diversos fatores, a acurácia desse exame não é perfeita, sendo comum a ocorrência de surpresas refrativas pós-operatórias, especialmente em pacientes com assimetria corneana, por exemplo, por conta de histórico prévio de cirurgia refrativa, pós-transplante de córnea, ectasias corneanas, entre outras. (2) São três as principais causas para erros na predição do poder da LIO em pacientes com cirurgia refrativa prévia: escolha da fórmula inadequada, erro na predição do poder corneano e erro do aparelho. (2) Pacientes previamente submetidos à cirurgia refrativa representam casos desafiadores e delicados quando se torna necessário proceder à FACO com implante de LIO, devido às alterações corneanas resultantes da primeira cirurgia.…”
Section: Introductionunclassified
See 1 more Smart Citation